Differentiation of hemispheric white matter lesions in migraine and multiple sclerosis with similar radiological features using advanced MRI - John, Flóra; Kis-Jakab, Gréta; Komáromy, Hedvig; Perlaki, Gábor; Orsi, Gergely; Bosnyák, Edit; Rozgonyi, Renáta; Trauninger, Anita; Eklics, Kata; Kamson, David Olayinka; Pfund, Zoltán (Frontiers in Neuroscience, 2024)
Abstract Background and aim. White matter hyperintensities (WMHs), presented on T2-weighted or fluid-attenuated inversion recovery magnetic resonance imaging (MRI) sequences, are lesions in the human brain that can be observed in both migraine and multiple sclerosis (MS). Methods. Seventeen migraine patients and 15 patients with relapsing-remitting multiple sclerosis with WMHs, and 17 healthy subjects age- and sex-matched to the migraine group were prospectively enrolled and underwent conventional and advanced MRI studies with diffusion- and perfusion-weighted imaging and single voxel proton magnetic resonance spectroscopy. Results. In both disease groups, elevated T2 relaxation time, apparent diffusion coefficient (ADC) values, and decreased N-acetyl-aspartate levels were found in the intralesional white matter compared to the contralateral normal-appearing white matter (NAWM), while there was no difference between the hemispheres of the control subjects. Migraine patients had the lowest intralesional creatine + phosphocreatine and myo-inositol (mI) values among the three groups, while patients with MS showed the highest intralesional T1 and T2 relaxation times, ADC, and mI values. In the contralateral NAWM, the same trend with mI changes was observed in migraineurs and MS patients. No differences in perfusion variables were observed in any groups. Conclusion. Our multimodal study showed that tissue damage is detectable in both diseases. Despite the differences in various advanced MRI measures, with more severe injury detected in MS lesions, we could not clearly differentiate the two white matter lesion types.